A Potential Avenue for Academic Success: Hope Predicts an Achievement-Oriented Psychosocial Profile in African American Adolescents. (September 2018) - Dixson, Dante D.; Stevens, David
In a sample of 117 African American students, we examined how well hope predicts five psychosocial variables—school belonging, academic self-concept, goal valuation, attitude toward teachers, and academic motivation/self-regulation—that altogether make up an achievement-oriented psychosocial profile. Results indicated that, after controlling for demographics and previous achievement, the subscales of hope accounted for a meaningful portion of all five psychosocial variables, ranging from 17.2% to 29.9%. The agency subscale of hope was a significant predictor of all five psychosocial variables, while pathways was only a significant predictor of goal valuation and academic self-concept. Given that several quick and effective universal hope interventions have been developed, these results suggest that hope may be a promising avenue to improve the achievement-related outcomes of African American students as well as aid in mitigating the achievement gap.